Get with the guidelines: management of chronic obstructive pulmonary disease in emergency departments in Europe and Australasia is sub‐optimal. Issue 2 (9th February 2020) - Kelly, Anne‐Maree; Van Meer, Oene; Keijzers, Gerben; Motiejunaite, Justina; Jones, Peter; Body, Richard; Craig, Simon; Karamercan, Mehmet; Klim, Sharon; Harjola, Veli‐Pekka; Verschuren, Franck; Holdgate, Anna; et al.
Abstract: Background: Exacerbations of chronic obstructive pulmonary disease (COPD) are common in emergency departments (ED). Guidelines recommend administration of inhaled bronchodilators, systemic corticosteroids and antibiotics along with non‐invasive ventilation (NIV) for patients with respiratory acidosis. Aim: To determine compliance with guideline recommendations for patients treated for COPD in ED in Europe (EUR) and South East Asia/Australasia (SEA) and to compare management and outcomes. Methods: In each region, an observational prospective cohort study was performed that included patients presenting to ED with the main complaint of dyspnoea during three 72‐h periods. This planned sub‐study included those with an ED primary discharge diagnosis of COPD. Data were collected on demographics, clinical features, treatment, disposition and in‐hospital mortality. We determined overall compliance with guideline recommendations and compared treatments and outcome between regions. Results: A total of 801 patients was included from 122 ED (66 EUR and 46 SEA). Inhaled bronchodilators were administered to 80.3% of patients, systemic corticosteroids to 59.5%, antibiotics to 44 and 60.6% of patients with pH <7.3 received NIV. The proportion administered systemic corticosteroids was higher in SEA (EUR vs SEA for all comparisons; 52 vs 66%, P < 0.001) as was administration of antibiotics (40 vs 49%, P = 0.02). Rates of NIV and mechanical ventilation were similar. Overall in‐hospital mortality was 4.2% (SEA 3.9% vs EUR 4.5%, P = 0.77). Conclusion: Compliance with guideline recommended treatments, in particular administration of corticosteroids and NIV, was sub‐optimal in both regions. Improved compliance has the potential to improve patient outcome.